Annual Research Review: Prevention of psychosis in adolescents – systematic review and meta‐analysis of advances in detection, prognosis and intervention. (14th September 2020) - Catalan, Ana; Salazar de Pablo, Gonzalo; Vaquerizo Serrano, Julio; Mosillo, Pierluca; Baldwin, Helen; Fernández‐Rivas, Aranzazu; Moreno, Carmen; Arango, Celso; Correll, Christoph U.; Bonoldi, Ilaria; Fusar‐Poli, Paolo
Abstract : Background: The clinical high‐risk state for psychosis (CHR‐P) paradigm has facilitated the implementation of psychosis prevention into clinical practice; however, advancements in adolescent CHR‐P populations are less established. Methods: We performed a PRISMA/MOOSE‐compliant systematic review of the Web of Science database, from inception until 7 October 2019, to identify original studies conducted in CHR‐P children and adolescents (mean age <18 years). Findings were systematically appraised around core themes: detection, prognosis and intervention. We performed meta‐analyses (employing Q statistics and I 2 test) regarding the proportion of CHR‐P subgroups, the prevalence of baseline comorbid mental disorders, the risk of psychosis onset and the type of interventions received at baseline. Quality assessment and publication bias were also analysed. Results: Eighty‐seven articles were included ( n = 4, 667 CHR‐P individuals). Quality of studies ranged from 3.5 to 8 (median 5.5) on a modified Newcastle–Ottawa scale. Detection : Individuals were aged 15.6 ± 1.2 years (51.5% males), mostly (83%) presenting with attenuated positive psychotic symptoms. CHR‐P psychometric accuracy improved when caregivers served as additional informants. Comorbid mood (46.4%) and anxiety (31.4%) disorders were highly prevalent. Functioning and cognition were impaired. Neurobiological studies were inconclusive. Prognosis : Risk for psychosis was 10.4% (95%CI: 5.8%–18.1%) at 6 months, 20% (95%CI: 15%–26%) at 12 months, 23% (95%CI: 18%–29%) at 24 months and 23.3% (95%CI: 17.3%–30.7%) at ≥36 months. Interventions : There was not enough evidence to recommend one specific treatment (including cognitive behavioural therapy) over the others (including control conditions) to prevent the transition to psychosis in this population. Randomised controlled trials suggested that family interventions, cognitive remediation and fish oil supplementation may improve cognition, symptoms and functioning. At baseline, 30% of CHR‐P adolescents were prescribed antipsychotics and 60% received psychotherapy. Conclusions: It is possible to detect and formulate a group‐level prognosis in adolescents at risk for psychosis. Future interventional research is required.